(untitled) (Linguamática, 2019)
The linguistic phenomena known as coreference and paraphrasing share certain aspects among themselves. It is common, for example, to refer to an entity in different ways within the same context, and as such the resolution of such coreferent mentions may be of aid to the process of identifying paraphrases. This paper presents an analysis of the capabilities of the coreference resolution tool CORP, created for use with the Portuguese language, within the context of paraphrase identification in the sentence and noun phrase levels.